EVALUATING CONTENTS VALUES OF PANCASILA STUDENT PROFILE IN THE TEXTBOOK OF ENGLISH “MY NEXT WORDS” OF SIXTH GRADE TO PRIMARY SCHOOL - Anggraeni , Dian Puspita; Wahyuni, Sri; Fitriati, Sri Wuli (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
Education aims to develop students' potential in line with Indonesia's vision of sovereignty, independence, and personality by fostering Pancasila values. The government has mandated the integration of the Pancasila Students’ profile into textbooks to prepare future leaders who embody these values and lead more effectively. This study’s objective is to evaluate English textbook in Primary School for Sixth Grade whether integrated with Pancasila Students Profile Students, know what the Pancasila Students’ profile values are in the textbook, and evaluate the quality of the textbooks according to BSKAP criteria with the 2024 Learning Outcomes. The research method is descriptive qualitative. The findings of this research are 1) the textbooks of Englis “My English Next Words” for sixth grade of Elementary school integrated Pancasila Profile Values in the form of text, image, and activity. Although, the integration mostly in the form of image, 2) there are sixth dimension of Pancasila Profile Students Values which presented both text and pictures; 1) devotion to and faith in God Almighty, 2) diversity of the world, 3) collaboration, 4) creativity, 5) critical thinking, and 6) independence, 3) the quality of English textbooks “My English Next Words” of sixth grade of Primary school is good. The textbook's incorporation of Pancasila values is evident and predominantly presented through images rather than text. This implies that there are opportunities to enhance the textual representation of these values to ensure a more balanced approach in conveying the Pancasila profile.